Strategi Penanganan Kawasan Permukiman Kumuh di Kelurahan Cibangkong Berdasarkan Konsep Livable Settlement - Tasya Salsha Safarina; Verry Damayanti (Bandung Conference Series: Urban & Regional Planning, 2023)
Abstract. The city is the center of government, activities and services which attracts residents to urbanize. An increase in the number of urban population that is not balanced with the increase in urban land can result in the emergence of slums. According to the Decree of the Mayor of Bandung Number: 648/Kep. 1227-DPKP3/2020 concerning Determination of Slum Housing and Slum Housing Locations in the City of Bandung, one of the sub-districts included in the list of slum housing and settlements is Cibangkong Village (RW 01, RW 06, RW 07, RW 10, and RW 12) slums with slum area of ​​49.9 Ha. In order for the house to provide a sense of security, comfort, peace and tranquility for its residents, it is necessary to apply the concept of livable settlement. The research variables used to identify the condition of slum areas are the physical condition of buildings, availability of open spaces, availability of settlement supporting infrastructure, pedestrian paths, range of public facilities, affordability of living costs, public transportation, and the role of stakeholders. The purpose of this study is to formulate a strategy for dealing with slum settlements in Cibangkong Village based on the concept of livable settlement. The approach method used is a mixed method to identify the conditions of slum settlements. The results of this study are strategies for dealing with slum settlements, namely improving the quality and maintenance of basic infrastructure, providing education regarding finance, providing venture capital, and/or skills to open businesses/services in improving people's welfare, establishing collaboration between government, academics, or experts to formulate proper handling. Abstrak. Kota adalah pusat pemerintahan, kegiatan, dan pelayanan yang menjadi daya tarik bagi penduduk untuk melakukan urbanisasi. Pertambahan jumlah penduduk perkotaan yang tidak seimbang dengan bertambahnya lahan perkotaan dapat mengakibatkan munculnya permukiman kumuh. Menurut SK Walikota Bandung Nomor: 648/Kep. 1227-DPKP3/2020 tentang Penetapan Lokasi Perumahan Kumuh dan Permukiman Kumuh di Kota Bandung, salah satu kelurahan yang masuk kedalam daftar perumahan dan permukiman kumuh adalah Kelurahan Cibangkong (RW 01, RW 06, RW 07, RW 10, dan RW 12) kumuh dengan luas kumuh 49,9 Ha. Agar rumah dapat memberikan rasa aman, nyaman, damai, dan tentram bagi penghuninya maka diperlukan penerapan konsep livable settlement. Variabel penelitian yang digunakan untuk mengidentifikasi kondisi kawasan kumuh yaitu kondisi fisik bangunan, ketersediaan ruang terbuka, ketersediaan prasarana penunjang permukiman, jalur pedestrian, jangkauan pelayanan fasilitas umum, keterjangkauan biaya hidup, transportasi umum, dan peran stakeholder. Tujuan dari penelitian ini yaitu untuk merumuskan strategi penaganan permukiman kumuh yang tepat di Kelurahan Cibangkong berdasarkan konsep livable settlement. Metode pendekatan yang digunakan adalah mixed method untuk mengidentifikasi kondisi permukiman kumuh. Hasil dari penelitian ini yaitu strategi penanganan permukiman kumuh diantaranya Peningkatan kualitas dan pemeriharaan infrastruktur dasar, memberikan edukasi mengenai finansial, pemberian modal usaha, dan atau keterampilan untuk membuka usaha/jasa dalam meningkatkan kesejahteraan masyarakat, menjalin kolaborasi antara pemerintah, akademisi, atau ahli untuk menyusun penaganan yang tepat.